2012
DOI: 10.1161/circinterventions.111.965749
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anemia on Long-Term Clinical Outcome in Patients Undergoing Revascularization With the Unrestricted Use of Drug-Eluting Stents

Abstract: Background— Anemia is frequent among patients with cardiovascular disease and adversely affects prognosis. The objective of this analysis was to assess the impact of anemia on long-term clinical outcomes among patients undergoing percutaneous coronary intervention (PCI) with the unrestricted use of drug-eluting stents (DES). Methods and Results— Between April 2002 to March 2009, 6528 consecutive patients underwent PCI with the unrestricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 33 publications
8
55
1
Order By: Relevance
“…However, other studies do not show that platelet or leukocyte counts at presentation are predictive of subsequent vascular events [12,14]. In contrast with the observations of a recent study [26], but in keeping with the findings of an earlier study on a similar population [12], multivariate analysis excludes an association between either cardiovascular risk factors or JAK2 mutation and subsequent vascular events. The results of the cumulative analysis conducted on combined thrombotic and hemorrhagic events (primary endpoint), explain at least in part, how cell dynamism contributes to vascular events in ET.…”
Section: Discussionmentioning
confidence: 48%
“…However, other studies do not show that platelet or leukocyte counts at presentation are predictive of subsequent vascular events [12,14]. In contrast with the observations of a recent study [26], but in keeping with the findings of an earlier study on a similar population [12], multivariate analysis excludes an association between either cardiovascular risk factors or JAK2 mutation and subsequent vascular events. The results of the cumulative analysis conducted on combined thrombotic and hemorrhagic events (primary endpoint), explain at least in part, how cell dynamism contributes to vascular events in ET.…”
Section: Discussionmentioning
confidence: 48%
“…Nikolsky et al [15] showed that anaemia predicted death in patients with myocardial infarction treated with primary angioplasty. Recently, Pilgrim et al [16] demonstrated that severe anaemia is common among patients undergoing PCI with the unrestricted use of drug eluting stent. Also, anaemia is associated with overall definite stent thrombosis (hazard ratio, 2.59; 95% confidence interval, 1.48-4.54; P=0.00089) and adversely affects long-term prognosis, including survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to bleeding, the incidence of atherothrombotic events is also higher in patients with anemia who undergo PCI (6). One obvious cause for this enhanced propensity is premature discontinuation of DAPT secondary to bleeding, which, particularly after implantation of drug-eluting stents (DES), is associated with higher incidence of probable or definite stent thrombosis (5,6). Furthermore, anemia secondary to subclinical malignancy or inflammatory processes is associated with other blood dyscrasias (13-15), which may predispose anemic patients to more ischemic events.…”
Section: Editorialmentioning
confidence: 99%
“…The existing data, almost exclusively from prospective analysis of clinical cohorts or retrospective post-hoc analysis of data from large randomized clinical trials designed to investigate other specific endpoints, point to anemia as a strong independent predictor of major adverse cardiac outcomes (MACE), major bleeding and mortality in patients undergoing PCI (4)(5)(6). Some of the published studies have utilized rigorous statistical methods to adjust for all known and measurable variables that can interact with anemia, nevertheless the associations inferred from these studies, while providing valuable insights, remain hypothesis generating.…”
mentioning
confidence: 99%
See 1 more Smart Citation